Synthesis and Evaluation of New Fluorinated Anti-Tubercular Compounds - Esfahanizadeh, Marjan (Shaheed Beheshti University of Medical Sciences, 2014)
Treatment of tuberculosis (TB) and the discovery of effective new anti-tubercular drugs are among the most urgent priorities in health organizations all over the world. In the present study, fluorinated analogs of some of the most important anti-TB agents such as p-aminosalicylic acid (PAS), thiacetazone and pyrazinamide were synthesized and tested against TB. The fluorinated analog of thiacetazone was 20 times more potent than the parent compound against M.tuberculosis H(37)-R(V), while the fluorinated p-aminosalicylic acid (PAS) was almost three times less potent than PAS. A few other halogenated analogs of thioacetazone were also synthesized and subjected to anti-M.tuberculosis screening tests. The best halogen substituent was found to be fluorine which has the smallest size from one hand and the strongest electronegativity from the other hand among the halogen atoms. Fluorine therefore could be considered as a golden substituent to improve the anti-M.tuberculosis activity of thioacetazone.